2022
DOI: 10.1002/advs.202105454
|View full text |Cite
|
Sign up to set email alerts
|

Open‐Source CFD Elucidating Mechanism of 3D Pillar Electrode in Improving All‐Solid‐State Battery Performance

Abstract: All‐solid‐state batteries (ASSBs) have become an important technology because of their high performance and low‐risk operation. However, the high interface resistance and low ionic conductivity of ASSBs hinder their application. In this study, a self‐developed electrochemical model based on an open‐source computational fluid dynamics platform is presented. The effect of contact area reduction at the electrode/solid‐state electrolyte interface is investigated. Then, a new conceptual 3D structure is introduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[168] Recently, Li et al investigated a new 3D pillar design for the ASSBs via the electrochemical model (Figure 13a). [169] The 3D pillar design could increase the contact area and enable the high utilization of active materials. However, the advantage of this structure is limited because of the increase of ohmic resistances as the height of the filler increases.…”
Section: D Current Collector and Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…[168] Recently, Li et al investigated a new 3D pillar design for the ASSBs via the electrochemical model (Figure 13a). [169] The 3D pillar design could increase the contact area and enable the high utilization of active materials. However, the advantage of this structure is limited because of the increase of ohmic resistances as the height of the filler increases.…”
Section: D Current Collector and Interfacementioning
confidence: 99%
“…For example, Chen et al reported a 3D lightweight, flexible copper-clad carbon framework (CuCF) as a current collector for Li metal anodes (Figure 13b). [172] The CuCF was fabricated by electroplating a Cu layer onto the surface of the carbon fiber, and the obtained [169] Copyright 2022, Wiley-VCH. b) Cross-sectional SEM image of a single carbon framework (CF) fiber coated with Cu layer.…”
Section: D Current Collector and Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The abundance and low cost of biomass-derived carbon make it an ideal candidate for use in supercapacitors [ 30 ], LIBs [ 31 ], and sodium ion batteries SIBs [ 15 ] to address the challenges mentioned above. Additionally, porous nanostructured carbon biomass can serve as an interface between the lithium electrode and the electrolyte, allowing charge to transfer [ 32 , 33 ]. A graphite electrode with a theoretical value of 372 mAh g −1 was determined, which is lower to fulfill the current demands.…”
Section: Introductionmentioning
confidence: 99%